“Together, well-organized, we are indomitable!”: Alexandra Kollontai and “the new woman” (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper presents the main segments of Alexandra Kollontai’s opus – her texts from periodicals, as well as her theoretical and fictional works. The paper is centered on her theory of “the new woman” and free love. It analyzes this author’s attitudes to relations between the sexes and the new morality, and the reactions that these attitudes of hers provoked. It particularly delves into her influence on the formation of a new female identity through periodical press. It provides an overview of the articles written by A. Kollontai and published in the following Soviet magazines – Работница, Коммунистка, Молодая гвардия, and Правда. Apart from that, the paper also points to the reception of her ideas in the Balkans, specifically in the magazine The Women's Movement. The last part of the paper deals with the literary works of A. Kollontai.
Keywords: Alexandra Kollontai; “the new woman”; Russian women’s periodicals; Marxist feminism; The Women’s Movement; Soviet Russia